Characterization and validation of hypothetical virulence factors in recently sequenced genomes of Magnaporthe species. (March 2023) - Bansal, Shilpi; Mallikarjuna, Mallana Gowdra; Reddy, Bhaskar; Balamurugan, Alexander; Achary, V. Mohan Murali; Reddy, Malireddy K.; Kumar, Aundy; Prakash, Ganesan
Abstract: Blast disease caused by Magnaporthe species is a major threat to the productivity of agriculturally important cereal crops including rice, pearl millet, wheat, oats, barley and minor millets etc . Two major species of Magnaporthe, viz . M. oryzae and M. grisea cause approximately 10–30% annual yield loss in their respective host crop. Imparting long-term resistance in the host necessitates the detailed knowledge on the molecular basis of pathogen virulence factors. Thus, here we have made an attempt to characterize the virulence factors (VFs) from M. grisea strain PMg-Dl in comparison to M. oryzae strain RMg-Dl. The functional gene ontology annotation revealed predominance of membrane system (GO: 0016020, GO:0016021), ion-binding system (GO:0043167; metal binding GO:0046872; zinc ion binding GO:0008270) etc. Further, in silico domain analysis of eight uncharacterized preferential virulence factor genes, viz . MBSD02000619.1.g3349, MBSD02000495.1.G5524, and MBSD02000009.1.G8852 and Mg.00g031250.m01, Mg.00g080210.m01, Mg.00g080580.m01, Mg.00g034390.m01 and Mg.00g016130.m01 showed the target genes belongingness to MFS family, integrase, protease, transcription factors etc. The PCR analysis showed the presence of eight target VFs in the Magnaporthe isolates infecting rice, pearl millet, finger millet and other grasses, respectively. The functional analysis of uncharacterized target preferential virulence factor genes ( M. oryzae :3; M. grisea: 5) in three host systems viz ., rice, pearl millet and finger millet at eight different time points confirmed their role as virulence factors in Magnaporthe system. The results are useful in further dissecting the Magnaporthe -host interactions by gene knock-out and knock in approaches through transgenics and genome editing to develop resistant cultivars soon. Highlights: Eight potential uncharacterized virulence factors (VFs) were identified from Magnaporthe species. Each VFs was a part of different protein family including MFS, integrase, receptor etc. The functional analysis of hypothetical genes confirmed their role as virulence factors in Magnaporthe system. VFs genes plays a key role in modulating the blast susceptibility in rice, pearl millet and finger millet hosts.